Pengaruh Insentif dan Lingkungan Kerja terhadap Kinerja Karyawan PT Pentasari Pranakarya Semarang - Veni Feriyanti; Riyono Riyono; Hesti Ristanto (Pusat Riset dan Inovasi Nasional, 2025)
Increasingly tight business competition, the performance of Human Resources owned by employees is required to continue to improve, in order to create human resources as assets whose productivity must be increased, to achieve this, the company must be able to create conditions that can encourage and enable comfort to develop and improve the abilities and skills they have optimally, one of the efforts that can be taken by the company to achieve these conditions is by providing incentives and a good work environment. The purpose of this research is to determine and analyze the influence of incentives and work environment on employee performance at PT Pentasari Pranakarya Semarang, which is located at Jl. Tambakaji I, No.1, Tambakaji Village, Ngaliyan District, Semarang City. The variables studied are the independent variables consisting of incentives and work environment. The dependent variable is employee performance. The sampling technique uses a saturated sample or census, namely taking the entire population as a sample, as many as 182 employees. The data collection method uses a questionnaire, then the respondents' answers are scored using a Likert scale. The data analysis used in this method is multiple linear regression. The research results can be concluded that: 1). Incentives do not have a significant effect on the performance of PT Pentasari Pranakarya employees, 2). The work environment does not have a significant effect on the performance of PT Pentasari Pranakarya employees. 3). Incentives and work environment together have no effect on the performance of PT Pentasari Pranakarya employees.